2017
DOI: 10.3892/etm.2017.5663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iodine-131 radiotherapy on Th17/Tc17 and Treg/Th17 cells of patients with differentiated thyroid carcinoma

Abstract: Abstract. T helper 17 (Th17), T cytotoxic 17 (Tc17) and regulatory T (Treg) cells serve important roles in a number of inflammatory and autoimmune diseases. The aim of the present study was to examine the distribution of Th17, Tc17 and Treg cells in patients with differentiated thyroid cancer (DTC) prior to as well as 7, 30 and 90 days following radioactive iodine-131 ( 131 I) therapy, and to elucidate the probable effects of 131 I therapy on Th17/Tc17 and Treg/Th17 cells in patients with DTC. A total of 40 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Decreased IL-17F and IL-21 after RAI ablation may prevent tumor invasion by reducing inflammation. Our results are consistent with Zhang et al, who reported an elevated frequency of Th17 cells in peripheral blood and their related serum cytokines in patients with DTC compared to healthy controls, a significant decline in these markers 2 week after 131 I therapy, and a return to normal levels after 3 months [36]. It is worth noting that, considering the complex interactions among cytokines within an extensive network, increased IL-10 alone or decreased IL-17 and IL-21 without affecting overall cytokine balance may not result in any specific biological effect [37] There is evidence in support of the beneficial effects of omega-3 on recovery in patients who undergo chemotherapy, radiotherapy, or both [38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Decreased IL-17F and IL-21 after RAI ablation may prevent tumor invasion by reducing inflammation. Our results are consistent with Zhang et al, who reported an elevated frequency of Th17 cells in peripheral blood and their related serum cytokines in patients with DTC compared to healthy controls, a significant decline in these markers 2 week after 131 I therapy, and a return to normal levels after 3 months [36]. It is worth noting that, considering the complex interactions among cytokines within an extensive network, increased IL-10 alone or decreased IL-17 and IL-21 without affecting overall cytokine balance may not result in any specific biological effect [37] There is evidence in support of the beneficial effects of omega-3 on recovery in patients who undergo chemotherapy, radiotherapy, or both [38].…”
Section: Discussionsupporting
confidence: 93%
“…Cytokines play a crucial role in the regulation of immune responses, and cytokine imbalances have been related with different diseases [8]. Changes in cytokines have been reported in patients with different types of cancers in previous studies [9,10], but the data are limited regarding cytokine alterations in thyroid cancer, and particularly after RAI ablation in patients with DTC [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Serum level of IL-17 increases significantly in patients with thyroid tumors compared with healthy controls (52,53). And its serum expression level of thyroid cancer is higher than that of thyroid adenoma, suggesting that it could be used as a potential biomarker to distinguish thyroid cancer from adenoma (54).…”
Section: Serum Interleukin Levelmentioning
confidence: 99%
“…IL17RA polymorphisms negatively correlated with the development of PTC [65]. The serum levels of IL-17 and the percentage of Th17, Tc17, and T regulatory cells (Tregs) were increased in patients with DTCs compared to healthy controls [66]. IL-17 and IL-23 expression in DTCs and MTCs were increased compared to thyroid adenoma, and IL-17 expression was associated with recurrence and mortality [67].…”
Section: Cytokinesmentioning
confidence: 99%